Measuring the Adequacy of Retirement Savings. (2nd August 2017) - Burnett, John; Davis, Kevin; Murawski, Carsten; Wilkins, Roger; Wilkinson, Nicholas
Abstract : This paper introduces four metrics for quantifying the adequacy of retirement savings, taking into account all major sources of retirement income. We then apply them to projections of expected future retirement income streams of a representative sample of the Australian population aged 40 and above. We find that omitting one or more pillars of savings significantly biases estimates of retirement savings adequacy. We also find that the four metrics are only weakly correlated with key commonly used indicators of financial well‐being, in particular current income and net worth. Our analysis also points to several shortcomings of the widely used income replacement ratio as an indicator of savings adequacy.